Relación entre la remuneración mínima vital con la canasta básica familiar en la región Loreto periodo 2017 2023 - Soria Tinedo, Dayanna Nohelia Crystal (2025)
The present research, titled “Relationship between the Minimum Living Wage the Basic Family Basket in the Loreto Region, 2017 – 2023”, it focuses on analyzing the interaction between two key economic well-being indicators in one of the most representative regions of the Peruvian Amazon. A quantitative approach was used, with a non-experimental and longitudinal design, allowing for the evaluation of hoy the evolution of the Minimum Living Wage (MLW) has influenced the cost of the Basic Family Basket over seven years. The análisis focused on monthly data for both the MLW and the Basic Family in Loreto, from 2017 – 2023. During this period, the MLW increased from S/. 850 in 2017 to S/. 1025 in 2023, representing a 20.59% rise. However, it was found that this increase has not been sufficient to cover the constant prise in the cost of the Basic Family Basket, which rose from S/. 1352 in 2017 to S/. 1784 in 2023 for an average family of four. This gap between income and the cost of living reflects a persistent issue of limited purchasing power, particularly in a region blike Loreto, where socioeconomic conditions and labor informality worsen the situation. The study's results show a significant correlation between the MLW and the cost of the Basic Family Basket, with a correlation coefficient of 0.78, indicating that increases in the minimum wage have a considerable impact on the variation of essential goods' prices.